Odpowiedzi

2010-03-12T17:59:52+01:00
X*11+(1200-x)*(11* 1/2 )=9350
x*11+1200*-x*60,5=9350
11+1200*+60,5=9350
11+1440000+60,5=9350

Najlepsza Odpowiedź!
2010-03-12T18:00:08+01:00
Rozwiązanie:
x * 11 + (1200 - x) * (11 * 1/2 ) = 9350
11x + (1200 - x) * 5,5 = 9350
11x + 6600 - 5,5x = 9350
11x - 5,5x = 9350 - 6600
5,5x = 2750 /:5,5
x = 500

sprawdzenie:
500 * 11 + (1200 - 500) * (11 * 1/2 ) = 9350
5500 + 700 * 5,5 = 9350
5500 + 3850 = 9350


daj naj. ;) pozdrawiam!
1 5 1
2010-03-12T18:17:39+01:00
X*11+(1200-x)*(11* 1/2 )=9350
11x+(1200-x)*5,5=9350
11x+6600-5,5x=9350
5,5x=2750 /÷5,5
x=500
1 4 1